A facile one-step hydrothermal approach for the synthesis of a CuMoO4/MoS2 composite as a high performance pseudocapacitive material for supercapacitor applications. (18th September 2019) - Kim, Hee-Je; Kim, Dong-Jin; Anitha, Tarugu; Yedluri, Anil kumar; Bak, Jin-Soo; Cho, Inho; Jagadeesh, M.; Reddy, Araveeti Eswar
Abstract : CuMoO4 /MoS2 -nanoparticle forest-like structures exhibit a very good specific capacitance and cyclic stability compared to the CuMoO4 and MoS2 electrodes. Abstract : In this study, CuMoO4, MoS2 -nanospheres and CuMoO4 /MoS2 -nanoparticle forest-like structures have been prepared using a controllable simple one step hydrothermal method. The specific capacitance was studied by using different electrochemical methods including cyclic voltammetry, galvanostatic charge/discharge tests and electrochemical impedance spectroscopic studies in 3 M KOH aqueous electrolyte. The results show that this unique nanoparticle forest-like structure merits superiorities such as large surface area, more accessible active sites, better infiltration/diffusion, high conductivity and high electrochemical/mechanical stability. The CuMoO4 /MoS2 -nanoparticle forest-like structures can achieve a relatively high specific capacitance of 1115.5 F g −1 at a current density of 2 A g −1 with a stable operational voltage of 0–0.5 V and a good capacitance retention of 90.42% at a current density of 4 A g −1 after 3000 cycles. The electrochemical properties are attributed to the good electrical conductivity, redox properties and synergistic effect of the two (CuMoO4 and MoS2 ) materials. This work demonstrates that the CuMoO4 /MoS2 composite is a promising electrode material for next-generation high-performance supercapacitor applications.